PROMETEUS N. 32 DEDICATED TO GRETA THUNBERG - Dinucci, Aldo (Prometheus - Journal of Philosophy., 2020)
Dear Greta Thunberg, In a world full of powerful men who make us ashamed of being humans, you bring back to us hope and faith in humanity. Many thanks, dear girl, for everything for everything you have been doing for us! We, editors of PROMETEUS, dedicate this edition to you. The Editors of PROMETHEUS.